Antifibrotic drugs as therapeutic tools in resistant melanoma - Berta Sanchez‐Laorden; M Angela Nieto (EMBO Molecular Medicine)
Abstract Melanoma is the most aggressive form of skin cancer. Together with the recent advances in immunotherapy, targeted therapy with inhibitors of the Mitogen Activated Protein Kinase (MAPKi) pathway including BRAF and MEK inhibitors has greatly improved the clinical outcome of these patients. Unfortunately, due to genetic and non‐genetic events, many patients develop resistance to MAPKi. Melanoma phenotypic plasticity, understood as the ability of melanoma cells to dynamically transition between different states with varying levels of differentiation/dedifferentiation, is key for melanoma progression. Lineage plasticity has also emerged as an important mechanism of non‐genetic adaptive melanoma drug resistance in the clinic (Arozarena & Wellbrock, 2019), highlighting the need for a deeper characterization of the mechanisms that control this process. In this issue of EMBO Molecular Medicine, Diazzi et al (2022) identify a mechanism regulating MAPKi‐induced phenotypic plasticity and resistance, providing evidence to support the use of an anti‐fibrotic drug as a potential novel combinatorial therapeutic approach.